Mathematical belief research in Finland - Pehkonen, Erkki; Hannula, Markku (NOMAD Nordic Studies in Mathematics Education, 2004)
In this paper we give a brief overview of the present state of belief research done in Finland. The Finnish research on mathematical beliefs has recently flourished because of three different sources of funding provided by the Academy of Finland: 1) a national graduate school for mathematics, physics, and chemistry teachers, 2) a series of international MAVI workshops, and 3) research projects on affective issues in mathematics. The Finnish research has contributed especially to understanding the development of beliefs during teacher education and to the development of theoretical foundation of belief research as well as some new methodological solutions.